La normalidad filosófica, un fenómeno educacional en movimiento - Sánchez Paredes, Carlos Miguel (2020)
The philosophical normality objectified by Romero turns philosophy in Latin America into an ordinary function of culture: philosophy becomes a common and professional activity in culture. As a consequence, it assumes an educational social function, committed to the education of the people, without undermining its vocation for knowledge and truth. Philosophical normality has a double educational aspect: a “conceptual”, which refers to philosophy as an intellectual activity that produces knowledge of certain characteristics; and the, "administrative", which implies an institutional exercise of philosophy, linked to educational entities or that are involved in the formal formal education system of the people.